Analysis of Carotenoid Content in Sea Grape (Caulerpa lentilifera) Cultivated with Low Plant Standing Different in The Basic Standard System - Arisqia, Neny; Amir, Sadikin; Rahman, Ibadur (Program Studi Budidaya Perairan Universitas Mataram, 2023)
Seaweed is one type of fishery commodity that is widely used both as a raw material for food, industry, medicine, and cosmetics. This causes the economic value of seaweed to help the community's economy and can increase the country's foreign exchange. Seaweed is one of the largest carotenoid producers because green seaweed generally contains chlorophyll a and b compounds and carotene compounds which can function as antioxidants. Factors that affect the content of carotenoids is the spacing of seaweed seeds. The purpose of this study was to determine the effect of spacing in the basic stake system on the carotenoid content of Caulerpa lentilifera and to determine the ideal spacing that gives optimal effect on the carotenoid content of Caulerpa lentilifera. This study used an experimental method with a completely randomized design (CRD) pattern with 6 treatments and 3 replications with treatments namely Control (25 cm spacing), P1 (20 cm spacing), P2 (30 cm spacing), P3 (20 cm spacing). plant 35 cm), P4 (planting distance 40 cm), P5 (planting distance 45 cm). The data obtained was then analyzed using variance (ANOVA) with a 95% confidence level and to find out the best growth a further test was carried out using the BNT test. The results showed that the spacing applied to the basic stake system had no effect on the carotenoid content of Caulerpa lentilifera, but had an effect on the absolute growth and specific growth rates. Spacing of 30 cm is the best distance for the growth of Caulerpa lentilifera with an absolute growth of 128.917 g and a specific growth rate of 4.965%, but the difference in spacing has no effect on the carotenoid content. The conclusion of this study was that the difference in plant spacing of the basic stake system had no effect on the carotenoid content of C. lentilifera, but had an effect on the absolute growth and specific growth rate. There was no ideal spacing to increase carotenoid content in C. lentilifera, because each treatment tended to have relatively the same carotenoid content.